EVALUATING SOLAR RADIATION POTENTIAL OF NORTH EAST USING ANGSTROM-PRESCOTT MODEL (FUDMA JOURNAL OF SCIENCES, 2025)
In this study, the model for estimating solar energy radiation potential in the north eastern Nigeria using Bauchi (Lat. 10o 18’ 48N; Lon 90 50’ 36E) as a case study was examined. The data on monthly average temperature, relative humidity, sunshine hours, atmospheric precipitation, hour angle, solar declination, and extra-terrestrial solar radiation were collected and analysed using Angstrom-Prescott model (APM): The metrological parameters were obtained from Bauchi airport between 2001 and 2010 (10 years). It was observed that the regression equation gives the highest values of R2 and least values of MBE, RMSE and MPE and provided the best estimate for the monthly mean average temperature, cloud cover (clearness index), and sunshine duration. It indicated a good agreement between the measured and estimated values for Bauchi state. Regression constants a0, a1 and R2 as 1.88, 0.00193 and 80.30 respectively for 2001-2010. The quantity of solar radiation in the study area is useful to engineers, hydrologists, architects and agriculturists in planning and executing projects.
Keywords: Solar Radiation Models; North east; Angstrom-Prescott; MBE; MPE; RMSE